Electrolyte and lithium ion battery using same
By introducing functional additive A into the electrolyte of lithium-ion batteries, the additive contains peroxy groups and sulfonyl groups, and constructing a CEI film, solving the problem of transition metal ions dissolution of the positive electrode material, and significantly improving the cycle stability and thermal stability of the battery.
Patent Information
- Application Number
- CN202411845401.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The positive electrode active material containing transition metal elements in lithium-ion batteries will dissolve transition metal ions during the cycle, resulting in increased internal resistance of the battery and structural damage, which will accelerate the attenuation of battery performance.
By introducing functional additive A into the electrolyte, the additive contains peroxy groups and sulfonyl groups, it is directly connected to form a special chemical environment, and builds a stable and dense CEI film, inhibits the dissolution of transition metal ions on the positive electrode surface, and regulates the physical structure and chemical components of the CEI film to improve lithium conductivity.
It effectively inhibits the dissolution of transition metal ions of the positive electrode material, reduces the concentration of these ions in the electrolyte, reduces unexpected reactions, delays the attenuation of battery capacity, and improves the cycle stability and thermal stability of the battery, especially under high voltage or high temperature conditions.
Smart Images

Figure BDA0005189613550000051 
Figure BDA0005189613550000061 
Figure BDA0005189613550000062
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery electrolytes, in particular to an electrolyte and a lithium ion battery using the electrolyte. Background Art
[0002] With the continued prosperity of the computer, communication and consumer electronics industries, the lithium-ion battery industry is experiencing rapid development. This trend is particularly evident in the rise of new energy vehicles in recent years. New energy vehicles have not only accelerated the evolution of power lithium-ion batteries, but also set unprecedented high standards for their energy density and safety performance. Among many performance indicators, the endurance of electric vehicles is particularly valued by consumers, and the battery energy density directly determines the vehicle's single mileage. Therefore, how to improve the battery energy density under limited space and weight conditions has become the focus of research inside and outside the industry. Among them, increasing the working voltage of the positive electrode material is regarded as one of the key ways to increase the energy density of lithium-ion batteries.
[0003] Positive electrode active materials containing transition metal elements, such as spinel (LNMO), ternary positive electrode materials, lithium cobalt oxide, layered lithium-rich oxide (LLO), etc., have higher operating voltages and show unique advantages in the field of lithium-ion batteries, but they also face some inherent technical challenges. Specifically, during the battery cycle, these positive electrode active materials will dissolve transition metal ions. The dissolution of transition metal ions not only consumes active substances and increases the internal resistance of the battery, but in severe cases will cause damage to the internal structure of the battery and accelerate the attenuation of battery performance. As the voltage of lithium-ion batteries continues to increase, the positive electrode material will have a higher electrode potential, and the oxidative decomposition of the electrolyte at the positive electrode and the positive electrode interface reaction will be more intense, which further dissolves transition metal ions from the positive electrode active material.
[0004] At present, researchers mainly overcome these defects by modifying the cathode materials, such as surface coating, designing the material microstructure, element doping, etc. However, these material modification methods have the defects of complex process and high cost. Summary of the invention
[0005] The object of the present invention is to provide an electrolyte and a lithium-ion battery using the same. The use of the electrolyte can improve the cycle capacity retention rate and average operating voltage of the lithium-ion battery under normal temperature and high temperature use environments, thereby improving the battery output characteristics.
[0006] According to one aspect of the present invention, an electrolyte is provided, including a functional additive A, wherein the molecular structure of the functional additive A satisfies Formula I: Wherein, R1 and R2 are each independently selected from substituted or unsubstituted alkyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted aryl; when substituted, the substituent includes at least one of an alkyl, an alkoxy, and a halogen atom.
[0007] This solution can improve the cycle stability and thermal stability of the battery using the electrolyte by introducing a functional additive A whose molecular structure satisfies Formula I into the electrolyte. The functional additive A contains both peroxide groups and sulfonyl groups, and the sulfonyl groups are directly connected to the peroxide groups to form a special chemical environment, so that the functional additive A can build a layer of CEI (solid electrolyte interface) film with stable structure, compactness and good conductivity on the surface of the positive electrode, thereby effectively inhibiting the dissolution of transition metal ions (TMs metal ions) from the positive electrode, and reducing the concentration of TMs metal ions in the electrolyte, thereby reducing the unexpected reaction between TMs metal ions and the electrolyte. Furthermore, it can also prevent TMs metal ions from migrating to the surface of the negative electrode, thereby reducing the damage of TMs metal ions to the negative electrode SEI film and reducing the deposition amount of TMs metal ions on the negative electrode, thereby improving the cycle stability and thermal stability of the battery. Secondly, by introducing functional additive A into the electrolyte, the physical structure and chemical composition of the CEI membrane can be regulated in situ, thereby improving the lithium conductivity of the CEI membrane, more efficiently transmitting lithium ions, reducing the polarization phenomenon of the battery during the cycle, slowing down the attenuation of the battery capacity, and especially improving the cycle capacity retention rate of the battery at high voltage or high temperature. In particular, after being used in a high-temperature environment, the transition metal elements in the positive electrode material are more easily dissolved into the electrolyte in the form of TMs ions; and the electrolyte provided by the present invention also has good heat resistance, and the CEI membrane formed by the functional additive A in a high-temperature environment still has good mechanical properties, improving the high-temperature cycle and high-temperature storage performance of the battery, and improving the capacity retention rate.
[0008] Preferably, the functional additive A includes methanesulfonic acid peroxyanhydride, bis(trifluoromethanesulfonic acid) peroxide, bis(benzenesulfonic acid) peroxide, bis(p-toluenesulfonic acid) peroxide, bis(4-(trifluoromethyl)benzenesulfonic acid) peroxide.
[0009] Preferably, the molecular structure of the functional additive A satisfies Formula II: Among them, R3~R 12 are each independently selected from hydrogen, alkyl, alkoxy, haloalkyl, haloalkoxy, and R3 to R 12The number of carbon atoms in the electrolyte does not exceed 10. After long-term experiments and verification, it was found that when the molecular structure of the functional additive A contains a benzene ring, and the benzene ring is directly connected to the sulfonyl group to form the structure shown in Formula II, the CEI membrane formed by the electrolyte has a dense structure that inhibits the dissolution of transition metal ions and excellent lithium conductivity, which helps to reduce the manganese deposition content of the negative electrode, prevent manganese ions from damaging the negative electrode SEI membrane, and thus reduce the consumption of active lithium. At the same time, it helps the rapid embedding and de-embedding of lithium ions in the positive and negative electrodes, thereby improving the cycle stability of the battery. In addition, by adjusting R3~R 12 Optimizing the number of carbon atoms in the electrolyte can effectively improve the stability of the electrolyte system and the structural stability of the CEI membrane.
[0010] Preferably, the functional additive A includes bis(benzenesulfonic acid) peroxide, bis(p-toluenesulfonic acid) peroxide, and bis(4-(trifluoromethyl)benzenesulfonic acid) peroxide.
[0011] Preferably, the functional additive A includes bis(benzenesulfonic acid) peroxide. The present invention selects bis(benzenesulfonic acid) peroxide as the functional additive A, and the electrolyte prepared thereby can effectively improve the cycle performance of the battery using the electrolyte in normal temperature and high temperature environments.
[0012] Preferably, based on the total mass of the electrolyte, the content of the functional additive A is 0.3-1%. The functional additive A within the above content range can improve the structural stability and thermal stability of the CEI membrane, effectively reduce the interface impedance, improve the battery cycle performance, delay battery aging, and extend the battery cycle life.
[0013] Preferably, the electrolyte further includes a sulfur-containing additive, and the sulfur-containing additive includes at least one of 1.3-propane sultone, 1,3-propylene sultone, and vinyl sulfate. Further, the introduction of the sulfur-containing additive into the electrolyte can promote the electrolyte to form a dense, flexible, and low-impedance CEI film on the surface of the positive electrode, which can form a compact structure layer without increasing the battery impedance, and improve the cycle performance and high-temperature performance of the lithium-ion battery.
[0014] Preferably, the mass ratio of the sulfur-containing additive to the functional additive A is 1-3:0.3-1.
[0015] Preferably, the content of the sulfur-containing additive is 0.5-3% based on the total mass of the electrolyte.
[0016] Preferably, the electrolyte includes an organic solvent, and the organic solvent includes cyclic carbonates, chain carbonates and chain carboxylates in a mass ratio of 1 to 15:20 to 75:5 to 20. As the main component of the electrolyte, the organic solvent needs to consider the compatibility with the entire system. The present invention selects cyclic carbonates, chain carbonates and chain carboxylates that meet the above-mentioned mass ratio requirements as organic solvents, which can provide a suitable medium for the functional additive A, so that the electrolyte has good chemical stability and relative dielectric constant, and the solvent has high compatibility stability with the aforementioned various additives, providing a stable and balanced mixed solvent system for lithium-ion batteries.
[0017] Preferably, the cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate (PC), and fluoroethylene carbonate (FEC).
[0018] Preferably, the linear carbonate includes at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).
[0019] Preferably, the chain carboxylic acid ester includes at least one of methyl acetate (MA), ethyl acetate (EA), methyl formate (MF), methyl propionate (MP), ethyl propionate (EP), methyl butyrate (MB), ethyl butyrate (EB), and ethyl difluoroacetate (DFAE).
[0020] Preferably, the chain carboxylate includes ethyl difluoroacetate (DFAE). Using DFAE as the chain carboxylate is conducive to the electrolyte participating in the circulation at a high working voltage, and can improve the wide temperature range performance of the electrolyte, and can also promote the CEI film formed by the functional additive A to have good flexibility and mechanical strength, thereby reducing the possibility of damage and cracking of the CEI film, and can effectively inhibit the dissolution of transition metal ions, effectively improving the cycle performance of the battery.
[0021] Preferably, the electrolyte further comprises a film-forming additive, and the film-forming additive comprises at least one of vinylene carbonate and fluoroethylene carbonate. By introducing the above-mentioned film-forming additive into the electrolyte containing the functional additive A, it is beneficial to improve the cycle stability of the positive electrode and the negative electrode at the same time. In the case where the functional additive A preferentially undergoes a redox reaction on the surface of the positive electrode, the above-mentioned film-forming additive will form an SEI film on the surface of the negative electrode. Through this complementary protection mechanism, it helps to enhance the structural stability of the SEI film and the CEI film, not only providing effective protection for the positive and negative electrodes, reducing unexpected reactions between the electrolyte and the electrodes, but also reducing the impedance of lithium ions passing through the positive and negative electrodes, improving the capacity retention rate of the battery, and delaying the cycle life of the battery.
[0022] Preferably, the content of the film-forming additive is 0.1-1% based on the total mass of the electrolyte.
[0023] Preferably, the electrolyte further comprises a lithium salt additive, the lithium salt additive comprising at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium dioxalate borate, and lithium difluorooxalate borate, and the content of the lithium salt additive is 0.5% to 1% based on the total mass of the electrolyte. Introducing the lithium salt additive in the above-mentioned addition amount into the electrolyte is conducive to improving the stability of the interface film, thereby improving the capacity retention rate and cycle performance of the battery, and can also improve the overall performance of the electrolyte and the uniformity of the electrolyte distribution in the battery, so as to ensure that the battery has good chemical stability and long life.
[0024] Preferably, the electrolyte includes electrolyte salt, and the content of the electrolyte salt is 10-15% based on the total mass of the electrolyte.
[0025] Preferably, the electrolyte salt is lithium hexafluorophosphate.
[0026] According to another aspect of the present invention, a lithium ion battery is provided, comprising a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode, and also comprising the above-mentioned electrolyte, wherein the active material of the positive electrode contains a transition metal element. By using the positive electrode active material containing transition metal elements in combination with the above-mentioned electrolyte, a uniform and dense CEI film can be formed on the positive electrode surface of the battery, which greatly optimizes the stability of the positive electrode interface, reduces the dissolution of transition metal ions, and at the same time enhances the lithium conductivity of the positive electrode, improves the lithium ion transmission efficiency, and thus enables the battery to maintain excellent cycle stability at a higher operating voltage.
[0027] Preferably, the active material of the positive electrode includes at least one of spinel lithium nickel manganese oxide positive electrode (LNMO), ternary positive electrode material, lithium cobalt oxide, layered lithium-rich oxide (LLO), and lithium-rich manganese-based oxide.
[0028] Preferably, the active material of the positive electrode comprises 0.25Li2MnO3·0.75LiMn 0.375 Ni 0.375 Co 0.25 O2. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides an electrolyte, which is composed of the following components:
[0032] Table 1. Raw material composition for preparing electrolyte in Example 1
[0033]
[0034]
[0035] Note: The ratios in Table 1 are all mass ratios, such as "1.3-propane sultone: 1,3-propene sultone = 1.5:0.5", that is, the mass ratio of 1.3-propane sultone to 1,3-propene sultone is 1.5:0.5, and the combination is used as a sulfur-containing additive.
[0036] Among them, the CAS number of bis(benzenesulfonic acid) peroxide is 29342-61-8, and its structural formula is:
[0037]
[0038] Among the above organic solvents, fluoroethylene carbonate (FEC) belongs to cyclic carbonate, diethyl carbonate (DEC) belongs to chain carbonate, and ethyl difluoroacetate (DFAE) belongs to chain carboxylate. Therefore, it can be calculated that the mass ratio of cyclic carbonate, chain carbonate and chain carboxylate is 10:75:15.
[0039] Prepare the raw materials according to the above-mentioned raw material composition, and prepare the electrolyte according to the following steps: in a glove box filled with argon, first mix the above-mentioned functional additive A, sulfur-containing additive, lithium salt additive, film-forming additive and organic solvent, then add electrolyte salt to the organic solvent, mix evenly at 10°C to obtain electrolyte.
[0040] Example 2
[0041] This embodiment prepares an electrolyte with reference to the preparation method provided in Example 1. The difference between this embodiment and Example 1 is that in the process of preparing the electrolyte, an equal mass of methanesulfonic acid peroxyanhydride is used to replace the functional additive A used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0042] Among them, the CAS number of methanesulfonic acid peroxyanhydride is 1001-62-3, and its structural formula is
[0043]
[0044] Example 3
[0045] This embodiment prepares an electrolyte with reference to the preparation method provided in Example 1. The difference between this embodiment and Example 1 is that in the process of preparing the electrolyte, an equal mass of bis(trifluoromethanesulfonic acid) peroxide is used to replace the functional additive A used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0046] Among them, the CAS number of bis(trifluoromethanesulfonic acid) peroxide is 4079-87-2, and its structural formula is
[0047]
[0048] Example 4
[0049] This embodiment prepares an electrolyte with reference to the preparation method provided in Example 1. The difference between this embodiment and Example 1 is that in the process of preparing the electrolyte, an equal mass of bis(p-toluenesulfonic acid) peroxide is used to replace the functional additive A used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0050] Among them, the CAS number of bis(p-toluenesulfonic acid) peroxide is 1886-68-6, and its structural formula is
[0051]
[0052] Example 5
[0053] This embodiment refers to the preparation method provided in Example 1 to prepare an electrolyte. The difference between this embodiment and Example 1 is that in the process of preparing the electrolyte, an equal mass of bis(4-(trifluoromethyl)benzenesulfonic acid) peroxide is used to replace the functional additive A used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0054] Among them, the CAS number of bis(4-(trifluoromethyl)benzenesulfonic acid) peroxide is 35673-10-0, and its structural formula is
[0055] Example 6
[0056] This embodiment refers to the preparation method provided in Example 1 to prepare an electrolyte. The difference between this embodiment and Example 1 is that in the process of preparing the electrolyte, the organic solvent uses fluoroethylene carbonate and ethyl difluoroacetate in a mass ratio of 10:15 as the organic solvent of this embodiment, that is, the organic solvent does not contain linear carbonate, and the remaining raw material ratios and preparation methods are strictly consistent with Example 1, especially the content of the organic solvent in the electrolyte.
[0057] Example 7
[0058] This embodiment prepares an electrolyte with reference to the preparation method provided in Example 1. The difference between this embodiment and Example 1 is that in the process of preparing the electrolyte, an equal mass of diethyl carbonate is used to replace the organic solvent used in Example 1, that is, the organic solvent is diethyl carbonate, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0059] Example 8
[0060] This example prepares an electrolyte by referring to the preparation method provided in Example 1. The difference between this example and Example 1 is that in the process of preparing the electrolyte, ethyl acetate of equal mass is used to replace the ethyl difluoroacetate used in Example 1, and the other raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0061] Example 9
[0062] This embodiment prepares an electrolyte with reference to the preparation method provided in Example 1. The difference between this embodiment and Example 1 is that in the process of preparing the electrolyte, an organic solvent of equal mass is used to replace the sulfur-containing additive used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0063] Comparative Example 1
[0064] This comparative example refers to the preparation method provided in Example 1 to prepare an electrolyte. The difference between this comparative example and Example 1 is that in the process of preparing the electrolyte, an equal mass of organic solvent is used to replace the functional additive A used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with Example 1.
[0065] Comparative Example 2
[0066] This comparative example refers to the preparation method provided in Example 1 to prepare an electrolyte. The difference between this comparative example and Example 1 is that in the process of preparing the electrolyte, an equal mass of methylene bis(benzenesulfonate) is used to replace the functional additive A used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with Example 1.
[0067] Among them, the CAS number of methylene bis(benzenesulfonate) is 1086266-03-6, and its structural formula is
[0068]
[0069] Comparative Example 3
[0070] This comparative example refers to the preparation method provided in Example 1 to prepare an electrolyte. The difference between this comparative example and Example 1 is that in the process of preparing the electrolyte, an equal mass of dibenzoyl peroxide is used to replace the functional additive A used in Example 1, and the remaining raw material ratios and preparation methods are strictly consistent with Example 1.
[0071] Among them, the CAS number of dibenzoyl peroxide is 94-36-0, and its structural formula is
[0072]
[0073] Preparation Example 1
[0074] The electrolytes provided in the above-mentioned Examples 1 to 9 and the electrolytes provided in Comparative Examples 1 to 3 were respectively used to prepare lithium-ion batteries (soft-pack batteries). The positive electrode, Celgard 2400 separator, and negative electrode were stacked in order, and a battery core was obtained by a lamination process. The battery core was placed in an outer packaging shell, dried, and injected with electrolyte. After vacuum packaging, standing, formation, and capacity separation processes, a lithium-ion battery was obtained.
[0075] The positive electrode includes a positive electrode current collector and a positive electrode active coating. The positive electrode current collector is aluminum foil. The positive electrode active coating includes a positive electrode active material 0.25Li2MnO3·0.75LiMn 0.375 Ni 0.375 Co 0.25 O2, conductive agent acetylene black, binder polyvinylidene fluoride (PVDF); in the positive electrode active coating, the mass ratio of positive electrode active material, conductive agent and PVDF is 94:3:3. The negative electrode includes a negative electrode collector and a negative electrode active coating, the negative electrode collector is copper foil, and the negative electrode active coating includes negative electrode active material graphite, conductive agent acetylene black, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR); in the negative electrode active coating, the mass ratio of graphite, conductive agent, CMC and SBR is 94:1:2:3.
[0076] Test Example 1
[0077] Test subjects: Lithium-ion batteries were prepared using the electrolytes provided in Examples 1 to 9 and Comparative Examples 1 to 3, respectively. The specific preparation method is shown in Preparation Example 1.
[0078] Test items and test methods:
[0079] (1) Normal temperature cycle performance test:
[0080] At 25°C, the lithium-ion battery is charged at a constant current of 0.5C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times at 25°C under the above conditions.
[0081] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0082] The average voltage (V) of a lithium-ion battery after N cycles = discharge energy of the Nth cycle / discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.
[0083] (2) High temperature cycle performance test:
[0084] At 45°C, the lithium-ion battery is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is subjected to 800 charge and discharge cycles at 45°C under the above conditions.
[0085] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0086] The average voltage (V) of a lithium-ion battery after N cycles = discharge energy of the Nth cycle / discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.
[0087] Test results: as shown in Table 2.
[0088] Table 2. Performance test results of this test case
[0089]
[0090] Result analysis:
[0091] Generally speaking, lithium-ion batteries experience capacity decay and a drop in average voltage after cycling. Therefore, by detecting the capacity retention rate of each battery after cycling, the cycle stability of the battery can be determined. By detecting the average voltage of each battery after cycling, the magnitude of the drop in the average voltage of the battery after cycling can be determined. This can further infer the cycle stability of the battery at a higher operating voltage, and whether there is structural collapse of the positive electrode material during the cycling process.
[0092] By comparing the test performance of Examples 1 to 9 with Comparative Examples 1 to 3 in Table 1, it can be found that the lithium ion batteries provided by Examples 1 to 9 have good cycle stability and thermal stability compared to the lithium ion batteries provided by Comparative Examples 1 to 3. Among them, the lithium ion battery provided by Example 1 has a high cycle capacity retention rate and average voltage under both normal temperature and high temperature use environments.
[0093] By comparing the comprehensive performance of the lithium ion batteries provided in Examples 1 to 9 with that in Comparative Examples 1 to 3, it can be found that, compared with the lithium ion batteries of Comparative Examples 1 to 3, the lithium ion batteries provided in Examples 1 to 9 have higher cycle capacity retention rates and average operating voltages under both normal temperature and high temperature use environments. This is because the functional additive A containing directly connected sulfonyl groups and peroxide groups in its molecular structure is introduced into the electrolyte provided in Examples 1 to 9, which effectively improves the cycle stability and thermal stability of the battery.
[0094] Among them, the electrolyte provided in Comparative Example 1 does not introduce functional additive A or materials with similar structures thereto. After the battery provided in Comparative Example 1 cycles 1000 times at room temperature or high temperature, the concentration of TMs metal ions in the electrolyte is high, and the battery exhibits poor cycle stability and low operating voltage. Comparative Example 2 introduces a compound containing a sulfonyl group but not a peroxide group into the electrolyte, and Comparative Example 3 introduces a compound containing a peroxide group but not a sulfonyl group into the electrolyte. Comparing the experimental data of Comparative Examples 1 to 3 with those of Example 1 shown in Table 2, it can be found that compared with the lithium ion battery of Comparative Example 1, the lithium ion batteries provided in Comparative Examples 2 to 3 have higher cycle capacity retention and average voltage at room temperature and high temperature; but the cycle stability and average voltage of the lithium ion battery of Example 1 at room temperature and high temperature are higher than those of the lithium ion batteries of Comparative Examples 2 to 3. This shows that when a sulfonyl group-containing compound is introduced into the electrolyte, or a peroxide group-containing compound is introduced into the electrolyte, the cycle stability and thermal stability of the corresponding lithium-ion battery can be improved, but the improvement is limited. When the functional additive A containing a directly connected sulfonyl group and a peroxide group in the molecular structure is introduced into the electrolyte, the cycle stability and thermal stability of the battery reach a good level, that is, the sulfonyl group and the peroxide group have a certain synergistic effect when they are directly connected, which can effectively reduce the concentration of TMs metal ions in the electrolyte.
[0095] By comparing the performance indicators of the lithium-ion batteries provided in Examples 1 to 5, it can be found that compared with the lithium-ion batteries of Examples 2 to 3, the lithium-ion batteries provided in Examples 1, 4, and 5 have better cycle stability and higher average voltage at high temperatures. That is to say, in Examples 1, 4, and 5, the functional additive A containing a benzene ring is introduced into the electrolyte, and the benzene ring in the functional additive A is connected to the peroxide group through a sulfonyl group, which helps to improve the cycle stability of the battery at room temperature and high temperature and slow down the attenuation of the operating voltage.
[0096] Comparing the lithium ion batteries provided in Example 1 with those in Examples 6 and 7, it can be found that the solvent of the electrolyte in Example 6 is a cyclic carbonate and a chain carboxylate, the solvent of the electrolyte in Example 7 is a chain carbonate, and the solvent of the electrolyte in Example 1 includes a chain carbonate, a cyclic carbonate, and a chain carboxylate. By comparing the performance in Table 2, it can be found that the battery cycle stability of Example 6 is similar to that of Example 7, but the cycle stability of the battery in Example 1 at both room temperature and high temperature is better than that of the battery in Example 6 and Example 7. This shows that there is a certain synergistic effect between the three chain carbonates, cyclic carbonates, and chain carboxylates, which can simultaneously improve the chemical stability, thermal stability, and relative dielectric constant of the electrolyte, thereby improving the cycle stability of the battery at both room temperature and high temperature.
[0097] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes a functional additive A, and the molecular structure of the functional additive A satisfies Formula I: Wherein, R1 and R2 are each independently selected from substituted or unsubstituted alkyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted aryl; when substituted, the substituent includes at least one of an alkyl, an alkoxy, and a halogen atom.
2. The electrolyte according to claim 1, characterized in that The molecular structure of the functional additive A satisfies Formula II: Among them, the R3~R 12 Each is independently selected from hydrogen, alkyl, alkoxy, haloalkyl, haloalkoxy, and said R3 to R 12 The number of carbon atoms in the molecule does not exceed 10.
3. The electrolyte according to claim 2, characterized in that The functional additive A includes bis(benzenesulfonic acid) peroxide.
4. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the content of the functional additive A is 0.3-1%.
5. The electrolyte according to claim 1, characterized in that The electrolyte includes an organic solvent, and the organic solvent includes a cyclic carbonate, a chain carbonate and a chain carboxylic acid ester in a mass ratio of 1 to 15:20 to 75:5 to 20.
6. The electrolyte according to claim 5, characterized in that The chain carbonate ester includes diethyl carbonate, and the chain carboxylic acid ester includes ethyl difluoroacetate.
7. The electrolyte according to claim 1, characterized in that The electrolyte further includes a sulfur-containing additive, and the sulfur-containing additive includes at least one of 1.3-propane sultone, 1,3-propene sultone, and vinyl sulfate.
8. The electrolyte according to claim 1, characterized in that The electrolyte further includes a film-forming additive, and the film-forming additive includes at least one of vinylene carbonate and fluoroethylene carbonate.
9. The electrolyte according to claim 1, characterized in that: The electrolyte also includes a lithium salt additive, which includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium dioxalatoborate, and lithium difluorooxalatoborate. The content of the lithium salt additive is 0.5% to 1% based on the total mass of the electrolyte.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode, and also comprises the electrolyte according to any one of claims 1 to 9, wherein the active material of the positive electrode contains a transition metal element.
Citation Information
Patent Citations
Nonaqueous electrolyte solution and electrochemical element using same
CN102934275A
Preparation method and application of 1, 3-propanedisulfonic anhydride
CN114702473A
Additive for lithium ion battery electrolyte, electrolyte and lithium ion battery
CN114784374A
Electrolyte for lithium ion battery and lithium ion battery containing electrolyte
CN116387622A
Lithium battery electrolyte and lithium battery
CN117954684A